El Nino And Determinants of The Output of Micro and Small Industry in Java - Siregar, Hermanto; Ahmad, Fahmi Salam; Hasanah, Heni; Pasaribu, Syamsul Hidayat (Indonesian Journal of Business and Entrepreneurship, 2020)
Micro and small industry sector plays an important role in the economy of a country including Indonesia, due to its large contribution to gross domestic product and its large labor absorption. The output of the sector is influenced by economic variables and non-economic factors such as the El Nino climate phenomenon. The purpose of this study is to analyze the impact of these economic factors and the climate phenomenon on the output of micro and small industries in Java by using panel data, which are combination of cross section and time series, i.e. 6 provinces of Java from 2011 to 2017. The results showed that these economic factors have positive effect on the output while El Nino has negative effect. In accordance with these results, the government needs to actively facilitate micro and small industries in the fulfillment of economic factors and assist the business actors in anticipating and mitigating the impact of El Nino. Keywords: Economic factors, El Nino, micro and small industry, panel data method